Influence of Learner Reflection on Academic Performance of Kenyan Secondary School Students - Ndiewo, Paul Oduor; Raburu, Pamela A.; Aloka, Peter J. O. (Scientific & Academic Publishing, 2016)
Academic performance of students at various levels of learning is a concern and many nations and scholars are looking for ways of alleviating the problem of poor academic performance. Academic performance among students may be a function of many factors such as their abilities, socio-economic background and pedagogical beliefs. This study investigated the influence of learners’ reflection on academic performance of secondary school students. The study was guided by Locke and Lotham’s achievement theory. Sequential explanatory design was adopted in the study. The target population of students was 2500. Stratified sampling was used to select 12 secondary schools while simple random sampling was used in this study to select 387 students and 12 form four class teachers. The researcher administered questionnaires and interview schedules to collect data. Content validity of the research instrument was enhanced through a pilot study using students not under the study. Reliability was determined by internal consistency method in which coefficient alpha of = 0.83 was obtained. Qualitative data was analyzed using thematic analysis while descriptive and inferential statistics such as Pearson product moment correlation were used to analyse quantitative data. A statistical significant relationship r = .17, p ≤ .05 was established between learner reflection and academic performance. The study recommended that school counselors should impress on parents and teachers the need to positively reinforce their students. In addition, teachers and school counsellors should equip students with social and self-awareness skills to help students adjust to learning environment.
Keywords: Learner reflection; Academic performance; Counselling; Secondary schools; Students